HARDWARE DESIGN AND IMPLEMENTATION OF THE WASTE MANAGEMENT SYSTEM ON PUBLIC FACILITIES (STUDY CASE: BANDUNG INSTITUTE OF TECHNOLOGY) - Nur Hidayati, Airinnisa
One of the consequences of population growth is the increasing amount of waste produced. This could lead to many problems if the management of waste is not done effectively. Waste management process includes trash collection on trash bins, trash distribution, and trash dumping on the landfills. The challenge to make waste management effective is the background for this final project. In this final project, the design of the waste management is carried out at the trash collection stage. This final project starts from identifying the user needs by collecting data from interviews and questionnaires to thy community of Bandung Institute of Technology. Based on these needs, functional and non-functional requirements specifications are defined. The functional requirements are; the system has several types of bins, the system can detect the type of garbage, the system can provide information about the flow of waste management in ITB, the system has an explanation of the waste category, the system can move trash to the correct containers, the system can provide information about the urgency of sorting waste, the system can identify users to give rewards, the system can detect the weight of the garbage collected, the system can display received reward information, the system can display statistics data from the weight of the garbage to analyze trash bin placement, the system can store historical data in the database, the system can send notifications when a trash bin is almost full or already full, the system can display the location of the trash bin and the status of the trash bin, and the system can open the lid of the trash bin automatically. For the non-functional needs of the system is divided into 3 main needs, namely supportability, usability, and reliability. To test this waste management system, a trash bin model which is divided into several subsystems is made, the subsystems are the garbage validation subsystem, the reward subsystem, the monitoring subsystem, the trash opening subsystem and the infographic subsystem. Based on these subsystems, inductive sensor is selected to detect metals, then LDR sensor to detect plastics, RFID module to identify users, ESP8266-01 module to communicate wirelessly, ultrasonic sensor to detect the trash’ heights, load cell sensor to detect the waste’s load, and a servo motor to move the bulkhead. In addition, there is an information system in the form of websites and mobile applications consisting of servers and databases for processing and storing data, an interface for displaying notifications when the trash bin is full and an interface to display the location of the trash bin. Results produced from the testing are; the system can validate trashes, the trash bin can open its lid automatically, the system can communicate with the internet and send data to the server, the system can manage data on the server, the system can store data to the data base, the system can show the interface of a notification when the trash bin is fully loaded, and the system can show the interface of the location to the trash bin in websites and the mobile application. This final project is done on a group. The main topic of this book is the hardware of the system. The software of the system is implemented by Fathia Andita Resapati.